Integrasi Penginderaan Jauh dan Sistem Informasi Geografis Untuk Analisis Suhu Permukaan Daratan di Kabupaten Manokwari. - Novita Kosamah; Abdul Muis Muslimin; Aries Astradhani Subgan (Jurnal Natural, 2026)
The development of urban areas in Manokwari Regency has the potential to reduce the availability of land containing vegetation or Green Open Space (GOS) which may be a contributing factor to increasing land surface temperature that triggers the Urban Heat Island (UHI) phenomenon. This study aims to estimate land surface temperature, analyze its relationship with land cover, and examine the pattern of temperature distribution in the four districts of the study area. The research method integrates remote sensing and Geographic Information Systems, using Landsat 8 OLI/TIRS imagery data, topographic maps, and land cover maps, which were analyzed in GIS through an overlay method and supported by field surveys. The results show that land surface temperatures range from 18.29–30.79°C with an average of 23.23°C and are dominated by the 25–30°C temperature class. Areas with extensive vegetation cover have lower temperatures, whereas residential and built-up areas have higher temperatures. Field surveys at 49 points indicate an average air temperature of 36.25°C with a low correlation to Landsat-derived temperatures (r = 0.34). The areal distribution of high temperatures is, in sequence: West Manokwari District, 2,201.560 ha (28.517%); South Manokwari District, 1,514.092 ha (5.891%); East Manokwari District, 413.156 ha (15.866%); and North Manokwari District, 184.431 ha (0.982%). West Manokwari District is the top priority for mitigating increasing land surface temperature, followed by East Manokwari District and South Manokwari District, through the development of GOS in built-up areas in Manokwari Regency.